Distribution and bioprospecting potential of actinobacteria from Indian mangrove ecosystems - Manikkam, Radhakrishnan; Pati, Premalata; Thangavel, Shanmugasundaram; Venugopal, Gopikrishnan; Joseph, Jerrine; Ramasamy, Balagurunathan; Dastager, Syed G. (Microbial Diversity in Ecosystem Sustainability and Biotechnological Applications, 2019)
Actinobacteria are the ecologically and economically important prokaryotes with the unprecedented ability to produce novel metabolites. They are widely distributed in nature due to their physiological and metabolic versatility. Actinobacteria from marine ecosystem are recognized as a promising source for novel bioactive metabolites. Notably, mangroves are the most fertile and productive marine ecosystem due to their ecophysiological conditions and vast microbial diversity. At the global level, there are many novel actinobacteria which have been reported from mangrove ecosystems and also explored for their bioprospecting potential. However, in India, microbiologists have explored actinobacteria from selected mangrove ecosystems for the past five decades with special reference to culturable diversity and antimicrobial, antimycobacterial, anticancer, and enzymatic activities. So far, around 22 rare actinobacterial genera have been reported from the Indian mangrove ecosystems. However, several other novel actinobacteria with promising bioprospecting potential are yet to be explored. Hence, research on actinobacteria in the Indian mangrove ecosystem is still in its infancy. This chapter will describe the exploratory research work carried out on the importance, diversity, antimicrobial and enzymatic activity, biodegradation, and nanotechnological potency of actinobacteria from the Indian mangrove ecosystems. This chapter will enable researchers to identify the gaps to be bridged for further research on Indian mangrove actinobacteria and exploit their potential to the maximum benefit to mankind.

Antibacterial and anti-HIV metabolites from marine streptomyces albus MAB56 isolated from Andaman and Nicobar Islands, India - Manikkam, Radhakrishnan; Murthy, Sangeetha; Palaniappan, Sivasankar; Kaari, Manigundan; Sahu, Amit Kumar; Said, Madhukar; Ganesan, Vijayalakshmi; Kannan, Sivakumar; Ramasamy, Balagurunathan; Thirugnanasambandan, Somasundaram; Dastager, Syed G.; Hanna, Luke Elizabeth; et al. (Applied Biochemistry and Biotechnology, 2023)
Marine-derived actinobacteria have tremendous potential to produce novel metabolites with diverse biological activities. The Andaman coast of India has a lot of microbial diversity, but it is still a relatively unknown ecology for isolating novel actinobacteria with beneficial bioactive compounds. We have isolated 568 actinobacterial strains from mangrove rhizosphere sediments and sponge samples. Crude extracts from 75 distinct strains were produced by agar surface fermentation and extracted using ethyl acetate. In the disc diffusion method, 25 actinobacterial strains showed antimicrobial activity; notably, the strain MAB56 demonstrated promising broad-spectrum activity. Strain MAB56 was identified as Streptomyces albus by cultural, microscopic, and molecular methods. Conditions for bioactive metabolites from MAB56 were optimized and produced in a lab-scale fermenter. Three active metabolites (C1, C2, and C3) that showed promising broad-spectrum antimicrobial activity were isolated through HPLC-based purification. Based on the UV, FT-IR, NMR, and LC-MS analysis, the chemical nature of the active compounds was confirmed as 12-methyltetradecanoic acid (C1), palmitic acid (C2), and tridecanoic acid (C3) with molecular formulae C14H28O2, C16H32O2, and C13H26O2, respectively. Interestingly, palmitic acid (C2) also exhibited anti-HIV activity with an IC50 value of < 1 mu g/ml. Our findings reveal that the actinobacteria from the Andaman marine ecosystems are promising for isolating anti-infective metabolites.
Keywords: actinobacteria; Andaman Islands; anti-HIV; Antibacterial; Bioactive metabolites

Novel finding: 2,4-Di-tert-butylphenol from streptomyces bacillaris ANS2 effective against mycobacterium tuberculosis and cancer cell lines - Kaari, Manigundan; Joseph, Jerrine; Manikkam, Radhakrishnan; Kalyanasundaram, Revathy; Sivaraj, Anbarasu; Anbalmani, Sivarajan; Murthy, Sangeetha; Sahu, Amit Kumar; Said, Madhukar; Dastager, Syed G.; Ramasamy, Balagurunathan (Applied Biochemistry and Biotechnology, 2023)
The aim of the present study is to identify actinobacteria Streptomyces bacillaris ANS2 as the source of the potentially beneficial compound 2,4-di-tert-butylphenol, describe its chemical components, and assess its anti-tubercular (TB) and anti-cancer properties. Ethyl acetate was used in the agar surface fermentation of S. bacillaris ANS2 to produce the bioactive metabolites. Using various chromatographic and spectroscopy analyses, the potential bioactive metabolite separated and identified as 2,4-di-tert-butylphenol (2,4-DTBP). The lead compound 2,4-DTBP inhibited 78% and 74% of relative light unit (RLU) decrease against MDR Mycobacterium tuberculosis at 100ug/ml and 50ug/ml concentrations, respectively. The Wayne model was used to assess the latent/dormant potential in M. tuberculosis H37RV at various doses, and the MIC for the isolated molecule was found to be 100ug/ml. Furthermore, the molecular docking of 2,4-DTBP was docked using Autodock Vinasuite onto the substrate binding site of the target Mycobacterium lysine aminotransferase (LAT) and the grid box was configured for the docking run to cover the whole LAT dimer interface. At a dosage of 1 mg/ml, the anti-cancer activity of the compound 2,4-DTBP was 88% and 89% inhibited against the HT 29 (colon cancer) and HeLa (cervical cancer) cell lines. According to our literature survey, this present finding may be the first report on anti-TB activity of 2,4-DTBP and has the potential to become an effective natural source and the promising pharmaceutical drug in the future.
Keywords: 2; 4-Di-tert-butylphenol; anti-cancer; Anti-tubercular; Molecular docking; Streptomyces bacillaris